A Discriminant Model For Skill Oriented Prediction of Female Cricketers Depending Upon Selected Performance Parameters - Sapna Mandoli; Deepak Sharma; Hem Chandra Joshi (Physical Education Theory and Methodology, 2021)
Research Purpose. The study aimed to develop a discriminant model for cricketers on the basis of physiological & anthropometric variables.